2022
DOI: 10.1161/jaha.121.023776
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Chronic Vasodilator Therapy in Patients With Vasospastic Angina

Abstract: Background Chronic vasodilator therapy with long‐acting nitrate is frequently used to treat vasospastic angina. However, the clinical benefits of this approach are controversial. We investigated the prognostic impact of vasodilator therapy in patients with vasospastic angina from the multicenter, prospective VA‐KOREA (Vasospastic Angina in KOREA) registry. Methods and Results We analyzed data from 1895 patients with positive intracoronary ergonovine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Although the clinical outcomes of each previous study were different from the outcomes of our study, which was composite clinical events including ACS, cardiac death, new-onset arrhythmia including VT and VF, and AV block, they showed that nicorandil had a neutral effect on adverse clinical outcomes and nitrates had a neutral effect or a tendency to increase the risk of adverse clinical outcomes. The most recent study using this VA-Korea registry [ 27 ] also showed that the risk of ACS at 2 years was significantly increased in the nitrate group compared with the non-vasodilator group (HR 2.49, 95% CI 1.01–6.14, p = 0.047) and that was not increased in the non-nitrate other type vasodilator group compared with the non-vasodilator group (HR 0.92, 95% CI 0.39–2.13, p = 0.841). However, composite clinical outcome including ACS, cardiac death, and new-onset arrhythmia at 2 years showed no significant differences between the nitrate, non-nitrate other type vasodilator, or non-vasodilator groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical outcomes of each previous study were different from the outcomes of our study, which was composite clinical events including ACS, cardiac death, new-onset arrhythmia including VT and VF, and AV block, they showed that nicorandil had a neutral effect on adverse clinical outcomes and nitrates had a neutral effect or a tendency to increase the risk of adverse clinical outcomes. The most recent study using this VA-Korea registry [ 27 ] also showed that the risk of ACS at 2 years was significantly increased in the nitrate group compared with the non-vasodilator group (HR 2.49, 95% CI 1.01–6.14, p = 0.047) and that was not increased in the non-nitrate other type vasodilator group compared with the non-vasodilator group (HR 0.92, 95% CI 0.39–2.13, p = 0.841). However, composite clinical outcome including ACS, cardiac death, and new-onset arrhythmia at 2 years showed no significant differences between the nitrate, non-nitrate other type vasodilator, or non-vasodilator groups.…”
Section: Discussionmentioning
confidence: 99%
“…A landmark study documented the capability of nicorandil to reduce the frequency of angina attacks in up to 75% of patients [ 153 ]. However, subsequent studies failed to demonstrate prognostic benefits of nicorandil [ 153 , 154 ]. Current guidelines support nicorandil use in case of refractory angina [ 1 ].…”
Section: Therapymentioning
confidence: 99%
“…Headache, dizziness and hypotension are the most common side effects, while mucosal and eye ulcerations are the most feared complications. Importantly, long-term therapy is not associated with tachyphylaxis [ 154 ].…”
Section: Therapymentioning
confidence: 99%
“…26 Several subsequent studies assessed the effects of nitrates on clinical outcomes in VSA patients, usually reporting increased or neutral risk of cardiovascular events compared with no nitrate therapy, as summarised in Table 1. [30][31][32][33][34][35] The lack of beneficial effects of nitrates on CAS-related events may be related to a loss of their vasodilator effects on constricted epicardial arteries due to the development of tolerance. 36 Furthermore, continuous exposure to nitrates may be associated with an impairment of endothelial function related to their release of nitric oxide molecules.…”
Section: Nitratesmentioning
confidence: 99%
“…Furthermore, as shown for chronic nitrate therapy, observational studies have yielded disappointing results about the efficacy of nicorandil in reducing clinical events in patients with VSA, also resulting in an increased rate of clinical events when combined with nitrates, as summarised in Table 1. 30,32,34 Thus, where available, nicorandil can be added to one or two CCBs, instead of nitrates, in case of symptom persistence. The usual dose is 10 mg nicorandil twice daily.…”
Section: Nicorandilmentioning
confidence: 99%